Reducing the Wheat Yield Gap Through Variety-Specific Management - A. de Oliveira Silva; A. K. Fritz; R. P. Lollato (Kansas Agricultural Experiment Station Research Reports, 2018)
In Kansas, wheat yields have been nearly stagnant at approximately 40 bu/a for the past 30 years, which corresponds to a yield gap (the difference between average producer yield and yield potential) of approximately 35 bu/a relative to the state average yield potential of ~75 bu/a. Our objective was to continue investigation on the influence of varieties with different genetic and agronomic characteristics and management practices on grain yield to demonstrate that appropriate variety-specific management can help producers to achieve long-term profitability in a sustainable manner. The Kansas State University wheat variety performance tests (VPT) evaluate 35–50 varieties in more than 20 locations every year. We have expanded the test to a paired-plot design in three VPT locations (Ellsworth, Conway Springs, and McPherson, KS) in the 2016–2017 growing season, where one plot is managed under standard management practice (SM) based on current farmer’s practice of each region with no fungicide application and the adjacent plot with the same variety is enhanced with additional 40 lb of N/a and two fungicide applications hereafter referred to as intensive management (IM). Yield gap between the IM and SM ranged from 7 bu/a in Conway to 10 bu/a in Ellsworth on average of all varieties, mainly due to stripe rust (Puccinia striiformisWestend) occurrence in the growing season. Varieties more susceptible to stripe rust had 50% cumulative probability yield gain of 9 bu/a across all locations studied by switching from SM to IM, while resistant varieties gained 7 bu/a. The probability of breakeven was 22% greater in susceptible varieties as compared to resistant varieties. Our results indicate that selecting varieties with resistance to major fungal diseases can narrow the wheat yield gap in most years, reducing the need for additional fungicide. By comparing yield responses of currently-grown and new wheat varieties under farmer’s management and intensive management practices, this on-farm research provides science-based information for farmers to maximize profit while protecting natural resources and reducing the wheat yield gap in Kansas.
Keywords: wheat yield gain; foliar fungal diseases; profitability; yield gap